Possible selves and the messy business of identifying with career - Bennett, Dawn; Freer, P. (International Society for Music Education, 2012)
There is general consensus that the working lives of musicians are diverse and complex, incorporating a wide range of activities and necessitating an attitude of lifelong learning. Whilst numerous music institutions have initiated curricular reform in recognition of the diverse and complex needs of graduates, the ability of faculty to engage students in a broad range of learning opportunities remains a problematic issue. This paper considers the development of students’ salient identities as a means of developing this motivation and engagement. Drawing on a small case study of undergraduate music performance and music education majors in Australia and the US, the paper introduces the concept of possible selves as an effective and broadly accessible tool for the training of musicians. Findings reveal that the limited definition of ‘musician as performer’ underpins the thinking of both performance and education students. At odds with students’ career and life plans, the performer definition appears to inhibit the development of holistic musician identities, with the result that many students present a personal definition of musician that is already too narrow to accommodate their developing career narratives.